Elaboración de una guía didáctica de danza autóctona que permita mejorar las habilidades y destrezas de los alumnos del 7mo año de educación básica en la escuela”Luis Felipe Borja” del cantón mejia, provincia de pichincha en el año lectivo 2011-2012. - Cueva Quiña, Hernán Alfonso (2013)
The present investigation has as purpose to create awareness among teachers and parents, through them, to transmit the students the importance of the autonomous dance and the benefits that will be obtained to be applied through the elaboration of a didactic guide that allows to improve abilities and skills, it should be noted that this will serve like a teaching-learning. It is important to rescue the value of movement in the educational context and therefore in the teaching-learning process because the movement is an aspect of the constituted dimension of human beings, and thereby it becomes an indispensable element to achieve an integral formation. Recreational activities can be considered as tools to improve the skills and abilities, is more than anything a learning for the student's adult life contributing the proper cognitive development as a basis for appropriate learning.